The argumentative dimension of metaphor and its persuasive role in the Prophetic discourse. - hamidat, djemai (El Omda in Linguistics and Discourse Analysis, 2025)
In light of the renewed interest in the rhetorical lesson in the modern era, which led to the emergence of a new َrhetoric based on defining the necessary relationship between rhetoric and studying the various means of persuasion that it employs, making argument - out of this interest - one of the most important theories that constitutes the interest of pragmatics as it is a feature in the speech and a character in it, especially as it includes all means of excitement, persuasion and dialogue, especially in the Holy Quran and the purified Sunnah. Therefore, the rhetorical field has got the attention of scholars, past and present, in the "rhetorical" image in general and the "metaphorical" image in particular in the prophetic speech as a means of argumentation that the Messenger, peace and blessings be upon him, used to consolidate a belief, replace a concept, modify a behavior or refute an opinion or suspicion, especially when the argument is based on an interactive perspective linked to the contexts of pragmatics and the status of communication.